2007
DOI: 10.1074/jbc.m702551200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Phototropic Signaling in Arabidopsis via Phosphorylation State Changes in the Phototropin 1-interacting Protein NPH3

Abstract: Phototropism, or the directional growth (curvature) of various organs toward or away from incident light, represents a ubiquitous adaptive response within the plant kingdom. This response is initiated through the sensing of directional blue light (BL) by a small family of photoreceptors known as the phototropins. Of the two phototropins present in the model plant Arabidopsis thaliana, phot1 (phototropin 1) is the dominant receptor controlling phototropism. Absorption of BL by the sensory portion of phot1 leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
189
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(206 citation statements)
references
References 93 publications
15
189
0
2
Order By: Relevance
“…The response in the presence of the inhibitor was very close to that of the phot1-5 rcn1-1 double mutant (Figure 6). A comparable experiment with the phot2-1 mutant showed only inhibition on treatment with cantharidin (see Supplemental Figure 4 online), confirming the results of Pedmale and Liscum (2007) for phot1-mediated phototropism.…”
Section: Treatment Of Etiolated Seedlings By a Pp2a Inhibitor Mimics supporting
confidence: 69%
“…The response in the presence of the inhibitor was very close to that of the phot1-5 rcn1-1 double mutant (Figure 6). A comparable experiment with the phot2-1 mutant showed only inhibition on treatment with cantharidin (see Supplemental Figure 4 online), confirming the results of Pedmale and Liscum (2007) for phot1-mediated phototropism.…”
Section: Treatment Of Etiolated Seedlings By a Pp2a Inhibitor Mimics supporting
confidence: 69%
“…This result indicated that the scaffold protein NPH3 modifies auxin transport in Arabidopsis roots by transducing the BL signal from phot1 and phot2 BL receptors. Pedmale and Liscum (2007) reported that NPH3 is in a phosphorylated state under dark conditions and that BL illumination causes NPH3 dephosphorylation via a phot1-dependent mechanism. Note that exposure to auxin stimulated NPH3 in the phosphorylated state, but the phosphorylation state of phot1 was not affected by auxin treatment (Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, even signaling elements acting downstream of a single phototropin appear to be required for a subset of phototropin responses. NPH3, RPT2 and PKS1 directly interact with phot1 suggesting that they act early in the pathway [22][23][24]. However none of them is required for all the phototropin responses that were tested [22][23][24].…”
Section: Phototropin Kinase Activity and Signal Transductionmentioning
confidence: 99%
“…NPH3, RPT2 and PKS1 directly interact with phot1 suggesting that they act early in the pathway [22][23][24]. However none of them is required for all the phototropin responses that were tested [22][23][24]. For example, NPH3 is required for phot1 and phot2-mediated phototropism, phot1-mediated leaf positioning but dispensable for chloroplast positioning and stomatal opening [22,25] (Figure 1).…”
Section: Phototropin Kinase Activity and Signal Transductionmentioning
confidence: 99%
See 1 more Smart Citation